Report of Oslerus rostratus (Strongylida: Filaroididae) in cats from the Canary Islands, Spain - Garcia-Livia, Katherine; Valladares Salmerón, Maria; Pacheco, Sandra; Valladares, Basilio; Foronda, Pilar (Austral Journal of Veterinary Sciences, 2022)
Metastrongylid species infecting wild and domestic cats worldwide are increasingly being reported. Between 2017 and 2019, a total of 202 faecal samples of domestic cats from the island of Tenerife (Canary Islands, Spain) were analysed by microscopy and molecular techniques. Morphological analyses showed that 8.91% (18/202) of the faecal samples presented first stage larvae (L1) of metastrongylid species. Total DNA was isolated and tested by PCR targeting a 508 bp fragment of the ITS-2 gene. The nucleotide sequences obtained showed high homology (100%) with the species Oslerus rostratus. This work contributes to the knowledge of the wide distribution of O. rostratus worldwide, being Tenerife (Canary Islands, Spain), close to the African continent, the new geographic location for this metastrongylid species. Further molecular studies involving new geographic areas from the island of Tenerife, as well as neighbouring islands, are needed to provide relevant insight and better understand the epidemiology of O. rostratus and other metastrongylid species in wild and domestic cats from the Canary Islands.